1982
DOI: 10.1161/01.atv.2.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma phosphatidylcholine/free cholesterol ratio as an indicator of risk for ischemic vascular disease.

Abstract: As part of a population survey and a follow-up study of plasma lipid profiles by high temperature gas-liquid chromatography, we have determined the quantities and relative proportions of all major chemical classes and molecular species of llpids of plasma from 1200 subjects at Visit 2 of the Toronto-McMaster Lipid Research Clinic Prevalence Study. We have compared these values between our 24 subjects with ischemic vascular disease and 73 control subjects matched for age, sex, and plasma total cholesterol and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Its importance lies in the hypothesis that an increased free cholesterol content of lipoproteins (relative to phospholipids) is an independent risk factor for coronary heart disease. 43 The mechanism by which this modi®cation could in¯uence the atherogenic process is not known. Speculation presently centres on the possibility that higher free cholesterol could decrease the¯uidity of the outer surface of lipoprotein subfractions thus in¯u-encing their participation in different metabolic processes (lipid exchange, lipolysis and receptor recognition).…”
Section: Discussionmentioning
confidence: 99%
“…Its importance lies in the hypothesis that an increased free cholesterol content of lipoproteins (relative to phospholipids) is an independent risk factor for coronary heart disease. 43 The mechanism by which this modi®cation could in¯uence the atherogenic process is not known. Speculation presently centres on the possibility that higher free cholesterol could decrease the¯uidity of the outer surface of lipoprotein subfractions thus in¯u-encing their participation in different metabolic processes (lipid exchange, lipolysis and receptor recognition).…”
Section: Discussionmentioning
confidence: 99%
“…25 In conclusion, the present study provides further support for the previously observed association of decreased plasma PC/FC ratios with ischemic vascular disease in humans. 6 Although early work had emphasized the protective effect against atherosclerosis of high phospholipid levels 26 and later the ratio of serum glycerophosphoNpids/free cholesterol had been proposed as an indicator of possible abnormalities in lipoprotein fluidity in disease, 27 there had been no specific measurements of the PC/FC ratios under controlled conditions. Recently Morrisett et al 28 have reported the total phospholipid and free cholesterol weight percentages of the HDL fraction of the C57BR/cdJ and CBA/J mice on a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…3 The mechanism of the implied infiltration of tissues by plasma lipids has remained obscure, although plausible theories have been advanced. 45 It has been recently reported 6 that in humans a decreased plasma phosphatidylcholine/free cholesterol ratio shows a higher correlation with ischemic vascular disease than does the plasma total cholesterol, or the high density lipoprotein cholesterol. In the present studies we have determined the plasma total lipid profiles in two inbred strains of mice, one of which develops significantly higher total cholesterol levels and significantly larger atheromatous lesions than the other on a high cholesterol diet.…”
mentioning
confidence: 99%
“…Such increase in the free cholesterol /lecithin ratio within the peripheral layer of lipoproteins has been shown to raise the risk for cardiovascular events possibly by reducing fluidity and stability of lipoproteins (Kuksis, 1982). Moreover, VLDLs from patients with type 1 diabetes have been shown, in vitro, to induce abnormal response of cellular cholesterol metabolism in human macrophages (Klein et al, 1989).…”
Section: Vldlsmentioning
confidence: 99%